Preparation method of coarse-grain-layer-free gold spraying wire

Through hot-top semi-continuous casting and optimized extrusion annealing process, the problem of formation of coarse crystal layer in the production of tin-zinc gold sprayed wire is solved, and an efficient and simplified preparation process is achieved, which improves the mechanical properties and production efficiency of gold sprayed wires.

CN119410902AActive Publication Date: 2025-02-11GUANGDONG INST OF NEW MATERIALS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411407839.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-02-11
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The existing production process of tin-zinc spray gold wire is complicated, resulting in abnormal growth of grain structure, forming a coarse crystal layer, reducing the mechanical properties of spray gold wire, and having problems of production efficiency and economic benefits.

Method used

The raw materials are prepared by casting gold-spraying wires by hot-top semi-continuous casting method, with a cooling rate of no less than 8℃/s, and then extruded at 180~250℃. By optimizing the cooling and extrusion process, the formation of a coarse crystal layer is avoided, and the After annealing at 120-180°C, pulling is performed.

Benefits of technology

The preparation steps are simplified, and the sprayed gold wire is prepared in a short process with high efficiency, avoiding the formation of a coarse crystal layer, improving the mechanical strength and elongation of the sprayed gold wire, reducing the line breakage rate, and improving production efficiency and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005077166510000071
    Figure BDA0005077166510000071
  • Figure BDA0005077166510000081
    Figure BDA0005077166510000081
  • Figure BDA0005077166510000082
    Figure BDA0005077166510000082
Patent Text Reader

Abstract

The invention belongs to the field of electronic materials, and particularly discloses a preparation method of a coarse-grain-layer-free gold spraying wire, which comprises the following steps: S1, melting preparation raw materials of the gold spraying wire, casting by adopting a hot-top semi-continuous casting method, and then cooling and forming at a cooling rate not lower than 8 DEG C / s to obtain a cast rod; and S2, the casting rod is subjected to extrusion forming at the temperature of 180-250 DEG C. According to the preparation method of the gold spraying wire, the rolling step is omitted, the preparation steps are more simplified, the gold spraying wire is efficiently prepared in a short process, the preparation process is green and low-carbon, meanwhile, the extrusion step is optimized, deformation energy storage of the material is reduced, a coarse grain layer is prevented from being formed in the gold spraying wire, the grain size and the size of a separated second phase are controlled, and the gold spraying wire is prepared. And the mechanical strength and the ductility of the gold spraying wire are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic materials, and in particular relates to a method for preparing a gold-spraying wire without a coarse crystal layer. Background Art

[0002] Metallized film capacitors are commonly used electronic devices. The quality of the end-surface gold spraying layer has an important influence on the life and charge-discharge performance of film capacitors. Tin-zinc alloy has a low melting point, excellent conductivity, low specific resistance, moderate strength, good plasticity, and is conducive to deformation processing. With the rapid development of lead-free electronic materials, the use of tin-zinc gold spraying wire has expanded rapidly.

[0003] At present, the main production process of tin-zinc spray gold wire includes the following steps:

[0004] 1) Casting: The ingot is produced by metal mold gravity casting, and the ingot diameter is generally 80mm-100mm;

[0005] 2) Extrusion: The ingot is heated and extruded to obtain a round rod blank. The diameter of the round rod blank is generally 6mm-15mm;

[0006] 3) Rolling: After annealing, the round bar blank is rolled into a wire rod blank, and the diameter is further reduced. The diameter of the wire rod blank is 3.5-4.5mm;

[0007] 4) Drawing: The rolled wire rod blank is annealed and then drawn into a gold-sprayed wire with a diameter of 1.0mm-3.2mm.

[0008] The above production methods have complicated procedures. The billet is deformed by extrusion and rolling. The grain structure is prone to abnormal growth, forming a coarse grain layer on the surface of the gold-spraying wire, which seriously reduces the mechanical properties of the gold-spraying wire. At the same time, the surface of the ingot produced by metal mold gravity casting is rough, the quality of the solidification structure is poor, and there are a large number of inclusions and pores. The round rod billet extruded by such an ingot has many pores and burr defects on the surface, and the wire breakage rate is high during rolling and drawing, which seriously affects the production efficiency and economic benefits. Summary of the invention

[0009] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a method for preparing a gold-spraying wire.

[0010] A second object of the present invention is to provide a zinc-tin gold-spraying wire.

[0011] The third object of the present invention is to provide a method for preparing a gold-sprayed wire and / or the application of the zinc-tin gold-sprayed wire in electronic devices.

[0012] In order to achieve the above object, the technical solution adopted by the present invention is:

[0013] A first aspect of the present invention provides a method for preparing a gold-spraying wire, comprising the following steps:

[0014] S1: After the raw materials for the gold spray wire are melted, they are cast by a hot top semi-continuous casting method, and then cooled and formed at a cooling rate of not less than 8°C / s to obtain a cast rod;

[0015] S2: Extruding the cast rod at 180-250°C.

[0016] Preferably, the cooling rate is 8-12°C / s, for example, it can be selected from 8°C / s, 8.5°C / s, 9°C / s, 9.5°C / s, 10°C / s, 10.5°C / s, 11°C / s, 11.5°C / s, 12°C / s or any value within the range of any two endpoints. The intensity of cooling during casting affects the grain size of the cast rod and the spacing of the secondary dendrite arms, and thus affects the tensile strength and elongation of the sprayed gold wire. In order to avoid the formation of coarse casting structure, the cooling intensity during casting is ≥8°C / s, so that the grain size of the cast rod is ≤150μm and the spacing of the secondary dendrite arms is ≤25μm.

[0017] In the present invention, the cast rod is extruded at 180-250°C, for example, it can be selected from 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C or any value within the range of any two endpoints. Extrusion is a key process that affects whether the gold-spraying wire forms coarse crystals. When the extrusion temperature is too low, the deformation energy storage of the material is large, and a coarse crystal layer is likely to appear. Therefore, the preparation method in the present invention needs to ensure that the extrusion molding temperature is 180-250°C. If the temperature is lower than 180°C, a coarse crystal layer is likely to appear. If the temperature is higher than 250°C, cracks are likely to form on the surface of the extruded product, and in severe cases, the product will directly break.

[0018] Preferably, the preparation method further comprises step S3, which is located after step S2, and the step S3 is: annealing at 120-180°C and then drawing. For example, the annealing temperature can be selected from 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C or any value within the range of any two endpoints. When the specifications of the product obtained after extrusion molding in step S2 meet the requirements of gold spraying wire, step S3 is not required; when the specifications of the product obtained after extrusion molding in step S2 do not meet the requirements of gold spraying wire, step S3 is required, and after further drawing in S3, gold spraying wire that meets the specification requirements is obtained.

[0019] Preferably, the annealing holding time is 1 to 3 hours, for example, can be selected from 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours or any value within the range of any two endpoints thereof.

[0020] Under the above annealing temperature and annealing time, the length of the precipitated phase in the microstructure of the annealed product is ≤20μm and the width is ≤3μm, which can improve the mechanical properties of the gold-sprayed wire after drawing. When the annealing temperature and the holding time are insufficient, the amount of the precipitated second phase is small, which is not conducive to improving the strength of the gold-sprayed wire. When the annealing temperature is too high or the holding time is too long, the size of the precipitated phase becomes larger, which is not conducive to improving the strength and elongation of the gold-sprayed wire.

[0021] Preferably, the diameter of the cast rod in step S1 is 80-154 mm, for example, it can be selected from 80 mm, 90 mm, 100 mm, 110 mm, 120 mm, 130 mm, 140 mm, 150 mm, 154 mm or any value within the range of any two of the above endpoints. If the specification of the cast rod is too large, that is, the diameter exceeds 154 mm, the temperature difference between the surface and the inside of the cast rod is too large, and low-melting-point tin-rich segregation nodules are likely to appear on the surface of the cast rod, resulting in serious segregation of the cast rod components, affecting subsequent extrusion. At the same time, the diameter of the cast rod exceeds 154 mm, the cooling rate of the center of the cast rod is low during solidification, the grains are coarse, and coarse grain rings are likely to appear during extrusion. If the specification of the cast rod is too small, that is, the diameter of the cast rod is less than 80 mm, the casting is difficult, and the melt is likely to solidify at the hot top position, resulting in casting failure.

[0022] Preferably, the diameter of the cast rod after processing in step S2 is 2.5 mm to 3.5 mm, for example, it can be selected from 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3 mm, 3.1 mm, 3.2 mm, 3.3 mm, 3.4 mm, 3.5 mm or any value within the range of any two endpoints thereof.

[0023] Preferably, the diameter of the gold-spraying wire is 1 to 3.2 mm, for example, can be selected from 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3 mm, 3.1 mm, 3.2 mm or any value within the range of any two of the above endpoints.

[0024] Preferably, the gold-spraying wire comprises a zinc-tin gold-spraying wire.

[0025] Preferably, the melting temperature in step S1 is 400-650°C, for example, it can be selected from 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C or any value within the range of any two endpoints. If the melting temperature is too high, it is easy to cause volatilization and burning of elements such as zinc and tin, thereby causing waste of raw materials.

[0026] Preferably, in the melting step in step S1, the metal material with a low melting point is first placed at the bottom of the heating furnace, and the metal material with a high melting point is placed at the top of the heating furnace, and the metal materials are heated to melt and mix.

[0027] Preferably, the casting step in step S1 uses a crystallizer whose cooling belt is made of graphite.

[0028] Preferably, the casting temperature in step S1 is 400-550°C, for example, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or any value within the range of any two endpoints. If the casting temperature is too high, it is easy to cause coarse grain structure of the cast rod, affecting the mechanical properties of the spray wire. If the casting temperature is too low, defects such as cold shut are easy to form on the surface of the cast rod.

[0029] Preferably, the step S1 is: heating the raw materials for preparing the gold-spraying wire to 400-650°C for melting, refining and filtering to obtain a melt; then casting the melt by a hot top semi-continuous casting method, and then cooling and forming it at a cooling rate of not less than 8°C / s; further preferably, preferably, the step S1 is: heating the raw materials for preparing the gold-spraying wire to 400-650°C for melting, refining and letting stand, and then filtering to obtain a melt; then casting the melt by a hot top semi-continuous casting method, and then cooling and forming it at a cooling rate of not less than 8°C / s.

[0030] Preferably, the refining is performed using at least one of high-purity nitrogen, high-purity argon, and a refining agent.

[0031] Preferably, the refining time is 5 to 15 minutes.

[0032] Preferably, the standing time is 10 to 30 minutes. The standing step is to allow the slag and gas to float, which is beneficial to remove the slag.

[0033] Preferably, the filtration adopts at least one of plate filtration and tube filtration.

[0034] Preferably, the filtering step adopts online filtration.

[0035] Preferably, the particle size of inclusions contained in the filtered melt does not exceed 1 μm.

[0036] Preferably, the proportion of the area of ​​the slag inclusions to the cross-sectional area of ​​the gold spraying wire does not exceed 5%.

[0037] The second aspect of the present invention provides a zinc-tin gold-sprayed wire, which comprises the following components in mass percentage: 20-90% tin and 10-80% zinc; the zinc-tin gold-sprayed wire is prepared by the preparation method of the gold-sprayed wire described in the first aspect of the present invention.

[0038] In the present invention, the mass percentage of tin in the zinc-tin gold-spraying wire is 20-90%, for example, it can be selected from 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or any value within the range of any two of the above endpoints.

[0039] In the present invention, the mass percentage of zinc in the zinc-tin gold-sprayed wire is 10-80%, for example, it can be selected from 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or any value within the range of any two of the above endpoints.

[0040] The zinc-tin gold-spraying wire comprises the following components in mass percentage: 20-89% tin, 10-79% zinc, and 0-5% trace elements which are not zero.

[0041] Preferably, the trace element is selected from at least one of copper and antimony.

[0042] Preferably, the zinc-tin gold-sprayed wire does not contain a coarse-grained layer.

[0043] Preferably, the tensile strength of the zinc-tin gold-sprayed wire is ≥173 MPa; further preferably, the tensile strength of the zinc-tin gold-sprayed wire is 173-200 MPa; even further preferably, the tensile strength of the zinc-tin gold-sprayed wire is 180.6-198.4 MPa.

[0044] Preferably, the yield strength of the zinc-tin gold-sprayed wire is ≥144 MPa; further preferably, the yield strength of the zinc-tin gold-sprayed wire is 144-180 MPa; even further preferably, the yield strength of the zinc-tin gold-sprayed wire is 161.1-173.5 MPa.

[0045] Preferably, the elongation after fracture of the zinc-tin gold-sprayed wire is ≥16.9%; further preferably, the elongation after fracture of the zinc-tin gold-sprayed wire is 16.9-30%; further preferably, the elongation after fracture of the zinc-tin gold-sprayed wire is 25.4-26.7%.

[0046] Preferably, the grain size of the zinc-tin gold-sprayed wire is ≤150 μm; further preferably, the grain size of the zinc-tin gold-sprayed wire is 119-145 μm.

[0047] Preferably, the secondary dendrite arm spacing of the zinc-tin gold-sprayed wire is ≤25 μm; further preferably, the secondary dendrite arm spacing of the zinc-tin gold-sprayed wire is 15.8-23 μm.

[0048] Preferably, the length of the second phase precipitated in the zinc-tin gold-sprayed wire is ≤23μm, and the width is ≤3.4μm; further preferably, the length of the second phase precipitated in the zinc-tin gold-sprayed wire is 15.4-23μm, and the width is 2.1-3.4μm; further preferably, the length of the second phase precipitated in the zinc-tin gold-sprayed wire is 15.4-20μm, and the width is 2.1-2.8μm.

[0049] The third aspect of the present invention provides a method for preparing the gold-sprayed wire described in the first aspect of the present invention and / or application of the zinc-tin gold-sprayed wire described in the second aspect of the present invention in electronic devices.

[0050] The beneficial effects of the present invention are as follows: the preparation method of the gold-sprayed wire in the present invention reduces the rolling step, the preparation steps are further simplified, and a short process and high-efficiency preparation of the gold-sprayed wire is achieved. The preparation process is green and low-carbon. At the same time, by optimizing the extrusion step, the deformation energy storage of the material is reduced, the formation of a coarse-grained layer in the gold-sprayed wire is avoided, the grain size and the size of the precipitated second phase are controlled, and the mechanical strength and elongation of the gold-sprayed wire are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a SEM image of the cross section of the tin-zinc gold-sprayed wire prepared in Example 1, magnified 50 times.

[0052] Figure 2 This is a SEM image of the cross section of the tin-zinc gold-sprayed wire prepared in Example 1, magnified 500 times.

[0053] Figure 3 This is a SEM image of the cross section of the tin-zinc gold-sprayed wire prepared in Example 1, magnified 10,000 times.

[0054] Figure 4 This is a SEM image of the cross section of the wire blank obtained after extrusion in Comparative Example 1, magnified 50 times.

[0055] Figure 5This is a SEM image of the cross section of the tin-zinc gold-sprayed wire prepared in Comparative Example 1, magnified 1000 times. DETAILED DESCRIPTION

[0056] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0057] In the hot top casting step (2) of Examples 1 to 10 of the present invention and Comparative Examples 2 to 4, cooling is performed using a crystallizer whose cooling belt is made of graphite, and the cooling medium is water.

[0058] Example 1

[0059] This example provides a method for preparing a tin-zinc gold-spraying wire without a coarse crystal layer, which comprises the following steps:

[0060] (1) Melting: Put the zinc ingot and tin ingot into the melting furnace, raise the temperature to 500°C after melting and stir evenly. Use high-purity nitrogen for refining for 10 minutes, stand and keep warm for 20 minutes after slagging to obtain a melt.

[0061] (2) The melt in step (1) was filtered using a 60-mesh ceramic filter plate, and a cast rod with a diameter of 90 mm was produced by hot top casting, wherein the casting temperature was 500° C. and the cooling rate was 12° C. / s.

[0062] (3) Extrusion: The ingot is heated and then extruded. The temperature of the ingot at the extrusion outlet is 210°C, and a ingot with a diameter of 3 mm is obtained.

[0063] (4) Drawing: The wire blank is annealed at 150°C for 1.5 hours and then air-cooled before being drawn to produce a gold-sprayed wire with a diameter of 1.8 mm, i.e., the tin-zinc gold-sprayed wire without a coarse grain layer in this example.

[0064] In the tin-zinc gold-spraying wire without a coarse-grained layer in this example, the mass percentage of tin is 30%, the unavoidable impurity elements are less than 0.1%, and Zn is the remainder.

[0065] Example 2

[0066] The preparation method of the coarse-grained layer-free tin-zinc gold-sprayed wire in this example is different from that in Example 1 only in that the cooling rate in step (2) of this example is 8° C. / s.

[0067] Example 3

[0068] The preparation method of the coarse-grained layer-free tin-zinc gold-sprayed wire in this example is different from that in Example 1 only in that the cooling rate in step (2) of this example is 10° C. / s.

[0069] Example 4

[0070] The preparation method of the coarse-grained tin-zinc gold-sprayed wire in this example is different from that in Example 1 only in that the wire billet temperature at the extrusion outlet in step (3) of this example is 240°C.

[0071] Example 5

[0072] The preparation method of the coarse-grained layer-free tin-zinc gold-sprayed wire in this example is different from that in Example 1 only in that the wire blank is annealed at 170° C. in step (4) of this example.

[0073] Example 6

[0074] The preparation method of the coarse-grained layer-free tin-zinc gold-sprayed wire in this example is different from that in Example 1 only in that the wire blank is annealed at 120° C. in step (4) of this example.

[0075] Example 7

[0076] The preparation method of the tin-zinc gold-sprayed wire without a coarse-grained layer in this example is different from that in Example 1 only in that the wire blank is kept warm for 1 hour in step (4) of this example.

[0077] Example 8

[0078] The preparation method of the tin-zinc gold-sprayed wire without a coarse-grained layer in this example is different from that in Example 1 only in that the wire blank is kept warm for 2 hours in step (4) of this example.

[0079] Example 9

[0080] The preparation method of the coarse-grained layer-free tin-zinc gold-sprayed wire in this example is different from that in Example 1 only in that the wire blank is annealed at 100° C. in step (4) of this example.

[0081] Example 10

[0082] The preparation method of the coarse-grained layer-free tin-zinc gold-sprayed wire in this example is different from that in Example 1 only in that the wire blank is annealed at 200°C in step (4) of this example.

[0083] Comparative Example 1

[0084] The preparation method of the tin-zinc gold-sprayed wire in this example is different from that in Example 1 only in that the ingot in step (2) of this example is cast by conventional gravity casting, the casting temperature is 600°C, and the cooling rate of the ingot during solidification is 6°C / s.

[0085] Comparative Example 2

[0086] The preparation method of the tin-zinc gold-sprayed wire in this example is different from that in Example 1 only in that the cooling rate in step (2) of this example is 6.5° C. / s.

[0087] Comparative Example 3

[0088] The preparation method of the tin-zinc gold-sprayed wire in this example is different from that in Example 1 only in that the wire billet temperature at the extrusion outlet in step (3) of this example is 160°C.

[0089] Comparative Example 4

[0090] The preparation method of the tin-zinc gold-sprayed wire in this example is different from that in Example 1 only in that the wire billet temperature at the extrusion outlet in step (3) of this example is 270°C.

[0091] The SEM images of the cross section of the tin-zinc sprayed gold wire prepared in Example 1 were magnified 50 times, 500 times and 10,000 times respectively by scanning electron microscopy. The test results are as follows: Figure 1 to Figure 3 The SEM image of the wire blank obtained after extrusion in Comparative Example 1 was tested by scanning electron microscopy. Figure 4 As shown, the SEM image of the cross section of the tin-zinc sprayed gold wire obtained after drawing in Comparative Example 1 was tested. Figure 5 As shown. Figure 1 It can be seen that when the cross section of the tin-zinc gold-sprayed wire prepared in Example 1 is magnified 50 times, the structure of the gold-sprayed wire is still uniform and dense, and no coarse crystal layer appears at the edge. Figure 2 It can be seen that when the cross section of the tin-zinc sprayed gold wire prepared in Example 1 is magnified 500 times, the precipitated phase ( Figure 2 The white in the middle is the precipitate phase, and the gray is the matrix) and the precipitate phase is evenly distributed, with an average length of about 8μm and a width of about 1μm. Figure 3 It can be seen that when the cross section of the tin-zinc sprayed gold wire prepared in Example 1 is magnified 10,000 times, oxide inclusions with a particle size of less than 1 μm can be observed (see Figure 3 The black part in the figure) and the precipitate phase (see Figure 3 The white part in the middle). Figure 4 It can be seen that the surface layer of the wire blank obtained by extrusion in Comparative Example 1 has bubble defects. Figure 5 It can be seen that the tin-zinc gold-sprayed wire prepared in Comparative Example 1 has defects such as inclusions and cracks.

[0092] The tin-zinc sprayed gold wires prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were cut open along the cross section, and polarized light observation was performed after electrolytic polishing and coating, and the data of grain size, secondary dendrite arm spacing, precipitated second phase size, and coarse grain layer thickness were statistically analyzed. A scanning electron microscope (SEM) was used to randomly photograph more than 10 fields of view of the sample, with a magnification of 1000 times. More than 5 second phases were randomly measured in the photos of each field of view, and then all the measured particle lengths and widths were averaged to obtain the size of the precipitated second phase.

[0093] The secondary dendrite arm spacing was measured by the line-intercepting method, and more than 10 fields of view of the sample were randomly photographed by a scanning electron microscope (SEM) with a magnification of 1000 times. More than 5 secondary dendrite arm spacings were randomly measured in each field of view, and then the ratio of all measured straight line lengths to the number of secondary diameter spacings was calculated to obtain the secondary diameter wall spacing.

[0094] The specific test results are shown in Table 1. The conditions of the preparation methods in Examples 1 to 10 and Comparative Examples 1 to 4 when drawing and preparing the tin-zinc sprayed gold wires are recorded, as shown in Table 1.

[0095] Table 1 Microstructure characteristics and drawing results of gold-sprayed wire

[0096]

[0097]

[0098] As can be seen from Table 1, compared with Comparative Example 1, Examples 1 to 10 of the present invention use the hot top casting method to replace the traditional gravity casting method, and the grain size, secondary dendrite arm spacing, and precipitation second phase size of the obtained tin-zinc gold-spraying wire are all smaller, and do not contain a coarse crystal layer. It can be drawn normally during the drawing process, and the wire breakage rate is extremely low. Compared with Examples 1 to 10, the cooling rate during casting in Comparative Example 2 is too low, and the grain size, secondary dendrite arm spacing, and precipitation second phase size of the obtained tin-zinc gold-spraying wire are all larger. There is also a coarse crystal layer in the gold-spraying wire, and a small amount of wire breakage occurs during the drawing process; the wire billet temperature at the extrusion outlet of Comparative Example 3 is too low, and there is a thicker coarse crystal layer in the obtained tin-zinc gold-spraying wire, and the wire breakage rate is high during drawing. The wire billet temperature at the extrusion outlet of Comparative Example 4 is too high, and the precipitation second phase size of the obtained tin-zinc gold-spraying wire is larger, there are cracks on the surface of the gold-spraying wire, and the wire breakage rate is high during drawing.

[0099] The mechanical properties of the tin-zinc gold-sprayed wires prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were tested respectively. The specific test methods are shown in Table 2 below.

[0100] Table 2 Mechanical properties test results of tin-zinc sprayed gold wire

[0101]

[0102]

[0103] It can be seen from Table 2 that, compared with comparative examples 1 to 4, the tin-zinc gold-sprayed wires prepared in embodiments 1 to 8 of the present invention have higher tensile strength, yield strength and elongation after fracture, specifically: the tensile strength is 180.6 to 198.4 MPa, the yield strength is 161.1 to 173.5 MPa, and the elongation after fracture is 25.4 to 26.7%.

[0104] In summary, compared with the traditional method, the tin-zinc gold-spraying wire preparation method of the present invention reduces the rolling step, the preparation step is more simplified, the short process is realized to prepare the gold-spraying wire, the preparation process is green and low-carbon, and at the same time, by optimizing the extrusion step, the deformation energy storage of the material is reduced, the formation of a coarse crystal layer in the gold-spraying wire is avoided, the grain size and the size of the precipitated second phase are controlled, and the mechanical strength and elongation of the gold-spraying wire are improved, so that the tensile strength of the prepared tin-zinc gold-spraying wire is 173-200MPa, the yield strength is 144-180MPa, and the elongation after fracture is 16.9-30%. In addition, the preparation method of the present invention controls the impurities in the gold-spraying wire through melt treatment and casting process optimization, significantly reduces the wire breakage rate during drawing, and improves production efficiency and economic benefits.

[0105] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for preparing a gold-spraying wire, characterized in that: The following steps are involved: S1: After the raw materials for preparing the gold spray wire are melted, they are cast by a hot top semi-continuous casting method, and then cooled and formed at a cooling rate of not less than 8°C / s to obtain a cast rod; S2: Extruding the cast rod at 180-250°C.

2. The method for preparing the gold-spraying wire according to claim 1, characterized in that: The preparation method further comprises step S3, which is located after step S2. Step S3 comprises: annealing at 120-180° C. and then drawing.

3. The method for preparing the gold-spraying wire according to claim 2, characterized in that: The annealing time is 1 to 3 hours.

4. The method for preparing the gold-spraying wire according to claim 1, characterized in that: The diameter of the cast rod in step S1 is 80-154 mm; and / or, the diameter of the cast rod after being processed in step S2 is 2.5 mm to 3.5 mm; And / or, the diameter of the gold-spraying wire is 1 to 3.2 mm.

5. The method for preparing the gold-spraying wire according to claim 1, characterized in that: The gold-spraying wire comprises a zinc-tin gold-spraying wire.

6. The method for preparing the gold-spraying wire according to claim 1, characterized in that: The melting temperature in step S1 is 400-650°C; And / or, the casting step in step S1 uses a crystallizer whose cooling belt is made of graphite; And / or, the casting temperature in step S1 is 400-550°C.

7. The method for preparing the gold-spraying wire according to claim 1, characterized in that: The step S1 is: heating the raw materials for preparing the gold spray wire to 400-650°C for melting, refining and filtering to obtain a melt; then casting the melt by a hot top semi-continuous casting method, and then cooling and forming at a cooling rate of not less than 8°C / s.

8. A zinc-tin gold-spraying wire, characterized in that: The zinc-tin gold-spraying wire comprises the following components in mass percentage: 20-90% tin and 10-80% zinc; the zinc-tin gold-spraying wire is prepared by the preparation method of the gold-spraying wire according to any one of claims 1 to 7.

9. The zinc-tin gold-spraying wire according to claim 8, characterized in that: The zinc-tin gold-spraying wire has at least one of the following characteristics: (a) the zinc-tin sprayed gold wire does not contain a coarse-grained layer; (b) the tensile strength of the zinc-tin sprayed gold wire is ≥173MPa; (c) the yield strength of the zinc-tin sprayed gold wire is ≥144MPa; (d) the elongation after fracture of the zinc-tin sprayed gold wire is ≥16.9%; (e) the grain size of the zinc-tin gold-sprayed wire is ≤150 μm; (f) the secondary dendrite arm spacing of the zinc-tin gold-sprayed wire is ≤25 μm; (g) The second phase precipitated in the zinc-tin gold-spraying wire has a length of ≤23 μm and a width of ≤3.4 μm.

10. A method for preparing the gold-sprayed wire according to any one of claims 1 to 7 and / or use of the zinc-tin gold-sprayed wire according to any one of claims 8 to 9 in electronic devices.

Citation Information

Patent Citations

  • Method for processing wire bar of zinc and zinc alloy

    CN101342548A

  • Pipe provided with corrosion prevention layer on the outside surface, process for production of the same, and process for production of alloy wires to be used for corrosion prevention of outside surface of the pipe

    CN101809183A

  • Anti-oxidation lead-free metal spraying material and preparation method thereof

    CN103060613A

  • Copper-zinc-tin alloy and manufacturing method therefor

    JP2007056365A